2017
DOI: 10.1042/bcj20170137
|View full text |Cite
|
Sign up to set email alerts
|

Loss of prion protein is associated with the development of insulin resistance and obesity

Abstract: Prion protein (PrP) was initially described due to its involvement in transmissible spongiform encephalopathies. It was subsequently demonstrated to be a cell surface molecule involved in many physiological processes, such as vesicle trafficking. Here, we investigated the roles of PrP in the response to insulin and obesity development. Two independent PrP knockout (KO) and one PrP overexpressing (TG20) mouse models were fed high-fat diets, and the development of insulin resistance and obesity was monitored. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…In addition, adenoviral E4orf1 protein (early region 4 open reading frame 1) was identified as a viral mechanism mediating acute adipogenesis in cells and animals [27,28]. Similarly, all other viruses and VLA listed in Table 1 have also been associated with obesity in animals and humans through pathological studies or epidemiological observations; however, other viral mechanisms (such as viral factors regulating inflammatory response and lipogenesis in adipose depots) directly engaged in adipogenic effects warrant further investigation [15,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45]. Notably, because phages do not directly infect animal cells, these bacterial viruses plausibly exert an adipogenic effect by affecting the symbiosis of microbiota [31,32,33,34].…”
Section: Viral Infectobesity: the Association Of Chronic Viral Infmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, adenoviral E4orf1 protein (early region 4 open reading frame 1) was identified as a viral mechanism mediating acute adipogenesis in cells and animals [27,28]. Similarly, all other viruses and VLA listed in Table 1 have also been associated with obesity in animals and humans through pathological studies or epidemiological observations; however, other viral mechanisms (such as viral factors regulating inflammatory response and lipogenesis in adipose depots) directly engaged in adipogenic effects warrant further investigation [15,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45]. Notably, because phages do not directly infect animal cells, these bacterial viruses plausibly exert an adipogenic effect by affecting the symbiosis of microbiota [31,32,33,34].…”
Section: Viral Infectobesity: the Association Of Chronic Viral Infmentioning
confidence: 99%
“…Notably, because phages do not directly infect animal cells, these bacterial viruses plausibly exert an adipogenic effect by affecting the symbiosis of microbiota [31,32,33,34]. The adipogenic observation in the patients of prion diseases (or coined as “slow viruses” previously), is plausibly ascribed to host immuno-metabolic adaptation to the chronic pathogenesis during disease progress, because no adipogenic effect has been associated to the prion protein [15,37,38,39,40,41,42]. In this context, we emphasize that host immuno-metabolic adaptation to prolonged viral infection comprises a common etiology for viral infectobesity.…”
Section: Viral Infectobesity: the Association Of Chronic Viral Infmentioning
confidence: 99%
“…Interestingly, prion protein (PrP C ), a mainly neuronal protein 14 – 16 , has been reported to influence glucose homeostasis in mouse models 17 19 and facilitate iron uptake by functioning as a ferrireductase (FR) partner for divalent metal transporters 20 . Though apparently disconnected, it is likely that PrP C modulates blood glucose by altering the expression of glucose transporter 2 (GLUT2) on pancreatic β-cells through iron, a bidirectional glucose transporter that regulates the release of insulin 21 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [69], Liu et al [70], Eltokhi et al [71], Cai et al [72], Pfeiffer et al [73], Lin et al [74], Royer-Zemmour et al [75], Pastor et al [76], Goodspeed et al [77], Zhang et al [78], Rogers et al [79], Su et al [80] and Foale et al [81] reported that NRXN1, CRHR1, SHANK2, PSEN2, CKB (creatine kinase B), CD200R1, SRPX2, PTPRZ1, SLC6A1, GABRB2, KCNA1, ASAH1 and LINGO1 were linked with progression of neuropsychiatric disorders, but these genes might be involved in advancement of obesity associated type 2 diabetes mellitus. Reports indicate that SPHK2 [82], NPC1L1 [83], CNTFR (ciliaryneurotrophic factor receptor) [84], SLC2A4 [85], EDA (ectodysplasin A) [86], TGM2 [87], GCK (glucokinase) [88], FASN (fatty acid synthase) [89], FAP ( broblast activation protein alpha) [90], PRNP (prion protein) [91], LYVE1 [92], SERPINE1 [93], TNF (tumor necrosis factor) [94], FASLG (Fas ligand) [95], HGF (hepatocyte growth factor) [96], FNDC5 [97], LBP (lipopolysaccharide binding protein) [98] and LOX (lysyl oxidase) [99] were found in obesity associated T2DM. Hirai et al [100], Vuori et al [101], Porta et al [102], Nomoto et al [103] and Blindbaek et al [104] demonstrates that VAMP2, CACNB2, SLC19A3, PFKFB3 and MFAP4 are essential for progression of type 1 diabetes, but these genes might be key for advancement of obesity associated type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%